PERAN PEMERINTAH DALAM REGULASI PERUNDANG-UNDANGAN WAKAF - Kasdi, Abdurrahman (UIN Sunan Kudus, 2015)
Waqf development is largely determined by the legal andregulatory certainty Legislation endowments. Therefore, the relevance andcontribution to the socio-political context to meet the objectives of legislation,and its relation to the various activities of the institution of waqf verynoteworthy. Likewise, how the political configuration contribution to theestablishment and improvement of the legal construction that can supportthe implementation of the endowment in order to improve the welfare of thepeople. The government’s role in strengthening the existence of endowmentsby issuing the Law perwakafan has been done; including in Egypt, startingfrom the Act. Egypt No. 10 Year 1911 and Law. Egypt No. 103 1961. Whilein Indonesia, the existence of endowments increasingly getting nowherewith the issuance of Government Regulation No. 28 Year 1977 on LandOwned perwakafan, which contains elements of substance and technicalperwakafan. Issuance of Government Regulation No. 28 In 1977 it createdthe updates are very important in the management of waqf property. Theseregulations provide for the legality of the exchange bolehnya waqf propertyafter obtaining permission from the Ministry of Religion. Other rules thatbring renewal in the management of waqf is a Presidential Instruction No. 1of 1991 concerning Islamic Law Compilation (KHI). Law No. 41 of 2004 onEndowments and PP 42 of 2006 on the Implementation of Law No. 41 of 2004.